A Prognostic Analysis of the Outcomes in Patients With Anti-γ-Aminobutyric Acid B Receptor Encephalitis - Chen, Weibi; Wang, Yunyun; Guo, Xiaoyuan; Gao, Lehong; Huang, Zhaoyang; Lin, Yicong; Xue, Qin; Liu, Gang; Zhang, Yan; Su, Yingying (Frontiers in Immunology, 2022)
Objective To evaluate neurological function and its influencing factors in patients with anti-γ -aminobutyric acid B receptor (GABABR) encephalitis. Methods This was a clinical cohort study of patients diagnosed with anti-GABABR encephalitis; long-term follow-up was performed by telephone. Clinical factors associated with prognosis were analyzed, including clinical manifestations, laboratory examinations, imaging features, tumor comorbidities and therapeutic responses. Results Twenty-two patients with anti-GABABR encephalitis were evaluated (median age: 55 years). Lung cancer was detected in eight patients. All were with serum tumor markers (mainly NSE), and three of them had additional onconeuronal antibodies. The patients with tumors were older than the patients without tumors and more likely to develop status epilepticus (62.5% vs. 14.3%; p = 0.052), central hypoventilation (50% vs. 7.1%; p = 0.039), and hyponatremia (87.5% vs. 14.3%; p = 0.001). The patients with tumors had higher mortality (87.5% vs. 0%; p < 0.05). Although 92.9% of the patients without tumors became functionally independent (mRS ≤2), sequelae of symptomatic seizures, neuropsychiatric symptoms, and cognitive impairment were still observed in 14.3%, 21.4%, and 21.4% of patients, respectively. Conclusions (1) Elderly patients with anti-GABABR antibodies, especially those with severe symptoms，serum tumor markers, and additional onconeuronal antibodies, should be screened for lung cancer. (2) Anti-GABABR encephalitis with tumors has a poor prognosis. (3) Most patients without tumors achieve self-care, but some still experience remaining neurological deficits.